SURVEI PENERAPAN PENDIDIKAN KARAKTER PADA MATA PELAJARAN PENJASORKES DI SMP NEGERI SE-KABUPATEN BOJONEGORO (STUDI PADA GURU PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN SE-KABUPATEN BOJONEGORO) - KURTUBI, IMAM (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In recent days, education is an important thing of social need, including for adults, teenagers, and kids. Unfortunately, the education in Indonesia is underestimated by common people. On the other hand, education is a principal thing that must be fulfilled in order to increase the life degree of Indonesian people so that the Indonesian may prevent by advancing other nations. Education takes the important role of social building and development. To increase this role, the education need to be supported by the development of science, technology, art, and educational organizing and qualifying that be done by some efforts, that is the implementation of character education.  The objectives of this study were as follows: (1) knowing the implementation of character education in physical education subject of State Junior High Schools in Bojonegoro; (2) knowing the obstacles of this implementation of character education in physical education subject of State Junior High Schools in Bojonegoro. The research design of this study was semi-structured interview. The sources of the data were SMP N 2 Ngasem, SMP N 2 Kalitidu, SMP N 1 Kalitidu, SMP N 2 Bojonegoro, dan SMP N 1 Bojonegoro. The results of the study that was done by the researcher were: (1) the learning process that was done in the State Junior High Schools in Bojonegoro, they were good in the planning aspect, most of them were not get any significant difficulties in the implementation aspect, and they had successfully grown up the positive character to their students in the evaluation aspect. (2) the obstacles of the character education implementation were the lack of the supporting facilities and the students inferior feeling. Based on the result of the study, it could be concluded that the survey to the implementation of character education of physical education subject in the State Junior High Schools in Bojonegoro is as follows: (1) the physical education subject teachers were implemented the character education well, (2) the students were increased in their presence in the physical education subject learning process. Keywords: implementation, character education, physical education teacher.